Fucoidans of Brown Algae: Comparison of Sulfated Polysaccharides from Fucus vesiculosus and Ascophyllum nodosum - Anatolii I. Usov; Maria I. Bilan; Nadezhda E. Ustyuzhanina; Nikolay E. Nifantiev (Marine Drugs, 2022)
Preparations of sulfated polysaccharides obtained from brown algae are known as fucoidans. These biopolymers have attracted considerable attention due to many biological activities which may find practical applications. Two Atlantic representatives of Phaeophyceae, namely, Fucus vesiculosus and Ascophyllum nodosum, belonging to the same order Fucales, are popular sources of commercial fucoidans, which often regarded as very similar in chemical composition and biological actions. Nevertheless, these two fucoidan preparations are polysaccharide mixtures which differ considerably in amount and chemical nature of components, and hence, this circumstance should be taken into account in the investigation of their biological properties and structure–activity relationships. In spite of these differences, fractions with carefully characterized structures prepared from both fucoidans may have valuable applications in drug development.